The effect of extrusion, fat coating and increased protein content of calf starter feed on growth performance of Angus calves and feedlot bulls - Orffer, Christiaan Johannes (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.